Mapping of genomic DNA loop organization in a 500-kilobase region of the Drosophila X chromosome by the topoisomerase II-mediated DNA loop excision protocol. - Iarovaia, O (1996)
The recently developed procedure of chromosomal DNA loop excision by topoisomerase II-mediated DNA cleavage at matrix attachment sites (S. V. Razin, R. Hancock, O. Iarovaia, O. Westergaard, I. Gromova, and G. P. Georgiev, Cold Spring Harbor Symp. Quant. Biol. 58:25-35, 1993; I. I. Gromova, B. Thompsen, and S. V. Razin, Proc. Natl. Acad. Sci. USA 92:102-106, 1995) has been employed for mapping the DNA loop anchorage sites in a 500-kb region of the Drosophila melanogaster X chromosome. Eleven anchorage sites delimiting 10 DNA loops ranging in size from 20 to 90 kb were found within this region. Ten of these 11 anchorage sites colocalize with previously mapped scaffold attachment regions. However, a number of other scaffold attachment regions are found to be located in loop DNA.